2016
DOI: 10.3748/wjg.v22.i20.4926
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic radiation force impulse imaging for assessing liver fibrosis in alcoholic liver disease

Abstract: ARFI is an accurate, non-invasive and easy method for assessing liver fibrosis in patients with ALD undergoing alcoholic detoxification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 45 publications
0
18
1
2
Order By: Relevance
“…Several studies with patients with liver diseases show a significant influence of alcohol consumption on elastography [30]. In our study on a random sample with healthy volunteers, we revealed no significant influence of alcohol on elastography.…”
Section: Discussioncontrasting
confidence: 51%
“…Several studies with patients with liver diseases show a significant influence of alcohol consumption on elastography [30]. In our study on a random sample with healthy volunteers, we revealed no significant influence of alcohol on elastography.…”
Section: Discussioncontrasting
confidence: 51%
“…We have come across very limited literature about ARFI elastography in alcoholic liver diseases, but it has been validated in liver fibrosis of other etiologies, namely, viral hepatic fibrosis, nonalcoholic steatohepatitis, etc., Two studies were available in the literature addressing the use of ARFI elastography in alcoholic liver fibrosis: one by Zhang et al in China (2014) on 112 patients and other by Kiani et al in France (2016) on 83 patients from deaddiction centers. [1819] In our study, we observed the SW velocity cutoffs of 1.37 m/s for significant fibrosis, 1.51 m/s for severe fibrosis, and 1.87 m/s for cirrhosis of liver. The cutoffs from meta-analysis were comparable to our study, whereas the observations of Zhang et al were lower and observations of Kiani et al were higher [Table 2].…”
Section: Discussionmentioning
confidence: 50%
“…pSWE can be used in HBV, HCV, hepatic toxicity, alcoholic liver disease, and autoimmune hepatitis related liver fibrosis[3739]. It can also be used as a screening tool for fibrosis detection at early stages[40], although evidence of benefit in this setting is limited.…”
Section: Clinical Applicationsmentioning
confidence: 99%